Analisis Audit Energi di Hotel Kota Malang Menggunakan Web-Based Monitoring System - Ahmad Hermawan; Rosina Ahda Dini; Chandra Wiharya (Elposys: Jurnal Sistem Kelistrikan, 2023)
Energy audits are evaluation activities carried out to determine the condition of the energy used in a system. Audits are carried out to provide the efficiency of an electrical system. The first energy audit conducted was the initial energy audit. By using the specifications of the installed electrical system and using monitoring data. Followed by a detailed energy audit, to determine the condition of a more specific electrical system. The data used is measurement/monitoring data, and data calculations are then compared with the provision of the electricity standard. In calculating the intensity of energy consumption in the initial energy audit process, the IKE Fave Hotel results were still by the standards with an IKE value of 213.59 kWh/m2. Meanwhile, based on the results of a detailed energy audit, it was found that the lighting system and cooling system were not up to standard because the lux results for several rooms showed results that were less than the lux standard. Thus, it is necessary to provide recommendations for improvements to the lighting and cooling system. Providing lighting recommendations can use dialux as a calculation comparison. In the lighting system, it is necessary to replace some of the lamp specifications installed because they are far from standard values. This also needs to be done on the cooling system, by replacing the installed air conditioner according to existing calculations. This replacement was carried out to save energy for the continuity of the hospitality industry process at Fave Hotel Malang.